2017
DOI: 10.31248/rjfsn2017.023
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural network for estimating the qualitative characteristics of cantaloupe melon and comparison with the regression model

Abstract: In this paper, the quality characteristics of melon was estimated by using color parameters and neural networks for three fertilizing stages (no fertilizer, fertilizing 5 and 10 ton/ha). For this purpose, chemical parameters including fructose, glucose and sucrose, and color parameters such as L*, a*, b* were studied. Physical characteristics under study were specific weight, mean firmness and skin. Chemical compositions include Brix, moisture content, titratable acidity, pH and ash. Results showed that the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A neural network was used to model the photosynthetic rate because of the ability of ANNs to explain the relationship between these and other parameters inside the greenhouse (Ouyang et al 2020). Some researchers have used prediction model techniques in different aspects of plant management, particularly for predicting total yield (Naroui Rad et al 2015;Ghasemi-Varnamkhasti et al 2018;Niazian et al 2018). The development of the photosynthetic rate prediction model using ANNs follows the stages (Graupe 2019;Malekian and Chitsaz 2021), as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…A neural network was used to model the photosynthetic rate because of the ability of ANNs to explain the relationship between these and other parameters inside the greenhouse (Ouyang et al 2020). Some researchers have used prediction model techniques in different aspects of plant management, particularly for predicting total yield (Naroui Rad et al 2015;Ghasemi-Varnamkhasti et al 2018;Niazian et al 2018). The development of the photosynthetic rate prediction model using ANNs follows the stages (Graupe 2019;Malekian and Chitsaz 2021), as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Many previous studies concerning the cultivation of melons have been reported, focusing on aspects such as climatic adaptation [8], crop rotation selection, and fertilizer type and management [9][10][11]. Different mathematical models have been analyzed for melon cultivation, in order to establish a precisive pattern of fertilizer application to improve the growth, quality, and resistance to pests and diseases [6,[12][13][14]. At present, in China, the fertilizer recommendations for melon cultivation are mostly based on empirical tables, results of soil nutrient analyses or field experiments.…”
Section: Introductionmentioning
confidence: 99%